Corrosion-resistant materials
The corrosion-resistant member employs a laminated structure of magnesium fluoride and aluminum fluoride layers to address the issue of peeling due to heat history, achieving enhanced durability and reduced particle generation in semiconductor manufacturing equipment.
Patent Information
- Application Number
- JP2021550483
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-04
- Filing Date
- 2020-09-03
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2040-09-03
AI Technical Summary
Existing corrosion-resistant coatings for semiconductor manufacturing equipment are prone to peeling off due to heat history, leading to reduced durability and increased particle generation.
A corrosion-resistant member with a metal substrate coated using a laminated structure of magnesium fluoride and aluminum fluoride layers, including a first and second crystalline layer sandwiching an amorphous layer, which enhances adhesion and resistance to thermal stress.
The proposed solution significantly reduces the likelihood of peeling and cracking of the corrosion-resistant coating even under repeated thermal cycles, thereby enhancing the member's corrosion resistance and reducing particle generation.
Smart Images

Figure 0007673639000002 
Figure 0007673639000003 
Figure 0007673639000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a corrosion-resistant member. [Background technology]
[0002] In semiconductor manufacturing processes, highly corrosive gases such as chlorine gas and fluorine gas may be used, and therefore corrosion resistance is required for components constituting semiconductor manufacturing equipment. Examples of components constituting semiconductor manufacturing equipment include chambers, piping, gas storage devices, valves, susceptors, shower heads, etc. Patent Document 1 discloses a showerhead or other component used in a semiconductor manufacturing process, which has an aluminum surface covered with a corrosion-resistant coating made of at least one of aluminum fluoride and magnesium fluoride.
[0003] Patent Document 2 discloses a vacuum chamber member having a corrosion-resistant coating formed on the surface of a substrate. The surface side of the corrosion-resistant coating is a layer mainly made of aluminum oxide or a layer mainly made of aluminum oxide and aluminum fluoride, and the substrate side of the corrosion-resistant coating is a layer mainly made of magnesium fluoride or a layer mainly made of magnesium fluoride and aluminum oxide. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 533368, 2005 [Patent Document 2] Japan Patent Publication No. 61410, 1999 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the members disclosed in Patent Documents 1 and 2 have a problem in that the corrosion-resistant coating is easily peeled off from the substrate due to thermal history. An object of the present invention is to provide a corrosion-resistant member having a corrosion-resistant coating that is not easily peeled off from a substrate even when subjected to a thermal history. [Means for solving the problem]
[0006] In order to solve the above problems, one aspect of the present invention is as follows [1] to [4]. [1] A metal substrate and a corrosion-resistant coating formed on a surface of the substrate, the corrosion-resistant coating is formed by laminating, in this order from the substrate side, a magnesium fluoride layer containing magnesium fluoride and an aluminum fluoride layer containing aluminum fluoride, the aluminum fluoride layer is a layer formed by laminating, in this order from the magnesium fluoride layer side, a first crystalline layer containing crystalline aluminum fluoride, an amorphous layer containing amorphous aluminum fluoride, and a second crystalline layer containing crystalline aluminum fluoride, the first crystalline layer and the second crystalline layer are layers in which diffraction spots are observed in an electron beam diffraction image obtained by irradiating the layers with an electron beam, The corrosion-resistant member is a layer in which a halo pattern is observed in an electron beam diffraction image obtained by irradiating the layer with an electron beam.
[0007] [2] The corrosion-resistant member according to [1], wherein the metal substrate is made of aluminum or an aluminum alloy. [3] The corrosion-resistant member according to [1] or [2], wherein the magnesium fluoride layer has a thickness of 100 nm or more and 1,000 nm or less. [4] The corrosion-resistant member according to any one of [1] to [3], wherein the aluminum fluoride layers have a total thickness of 200 nm or more and 50,000 nm or less. Effect of the Invention
[0008] In the corrosion-resistant member according to the present invention, the corrosion-resistant coating is unlikely to peel off from the substrate even when subjected to a thermal history. [Brief description of the drawings]
[0009] [Figure 1] 1 is a cross-sectional view illustrating a configuration of a corrosion-resistant member according to an embodiment of the present invention. [Diagram 2] 2 is an electron beam diffraction image obtained by irradiating a first crystalline layer of the corrosion-resistant member of FIG. 1 with an electron beam. [Diagram 3] 2 is an electron beam diffraction image obtained by irradiating an amorphous layer of the corrosion-resistant member of FIG. 1 with an electron beam. [Figure 4] 2 is an electron beam diffraction image obtained by irradiating a second crystalline layer of the corrosion-resistant member of FIG. 1 with an electron beam. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] An embodiment of the present invention will be described below. Note that this embodiment is merely an example of the present invention, and the present invention is not limited to this embodiment. In addition, various modifications and improvements can be made to this embodiment, and such modifications and improvements can also be included in the present invention.
[0011] 1, the corrosion-resistant member according to this embodiment includes a metal substrate 10 and a corrosion-resistant coating 30 formed on the surface of the substrate 10. The corrosion-resistant coating 30 is formed by laminating, in order from the substrate 10 side, a magnesium fluoride layer 31 containing magnesium fluoride (MgF2) and an aluminum fluoride layer 32 containing aluminum fluoride (AlF3).
[0012] The aluminum fluoride layer 32 is formed by laminating, in order from the magnesium fluoride layer 31 side, a first crystalline layer 32A in which the aluminum fluoride contained is crystalline, an amorphous layer 32B in which the aluminum fluoride contained is amorphous, and a second crystalline layer 32C in which the aluminum fluoride contained is crystalline.
[0013] 2 and 4, the first crystalline layer 32A and the second crystalline layer 32C are layers in which diffraction spots are observed in an electron beam diffraction image obtained by irradiation with an electron beam, and as shown in Fig. 3, the amorphous layer 32B is a layer in which a halo pattern is observed, preferably only a halo pattern, in an electron beam diffraction image obtained by irradiation with an electron beam.
[0014] The first crystalline layer 32A and the second crystalline layer 32C need only contain aluminum fluoride that is at least partially crystalline, and need not be entirely crystalline. The aluminum fluoride contained in the first crystalline layer 32A and the second crystalline layer 32C may be aluminum fluoride (AlF3), aluminum fluoride hydrate (AlF3·nH2O), aluminum fluoride partially containing hydroxyl groups (AlF 3-x (OH) x ), aluminum fluoride hydrate containing some hydroxyl groups (AlF 3-X (OH) X nH2O), aluminum fluoride containing some oxygen (AlF 3(1-X) O 3 / 2X ), and partially oxygenated aluminum fluoride hydrate (AlF 3(1-X) O 3 / 2X The amorphous aluminum fluoride contained in the amorphous layer 32B may be at least one selected from aluminum fluoride (AlF3), aluminum fluoride hydrate (AlF3·nH2O), aluminum fluoride partially containing hydroxyl groups (AlF 3-X (OH) X ), aluminum fluoride hydrate containing some hydroxyl groups (AlF 3-X (OH) X nH2O), aluminum fluoride containing some oxygen (AlF 3 (1-X) O 3 / 2X ), and partially oxygenated aluminum fluoride hydrate (AlF 3 (1-X) O 3 / 2X At least one selected from the group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32
[0015] The corrosion-resistant member according to the present embodiment has excellent corrosion resistance even in highly corrosive gases and plasmas because it is provided with the corrosion-resistant coating 30. In addition, since the magnesium fluoride layer 31 is interposed between the aluminum fluoride layer 32 and the substrate 10, the adhesion between the aluminum fluoride layer 32 and the substrate 10 is high. Furthermore, since the aluminum fluoride layer 32 has a sandwich structure in which the amorphous layer 32B is sandwiched between the first crystalline layer 32A and the second crystalline layer 32C, the corrosion-resistant coating 30 is unlikely to peel off from the substrate 10 and is unlikely to crack even when subjected to a thermal history. For example, even when subjected to a thermal history of repeated temperature increases and decreases, the corrosion-resistant coating 30 is unlikely to peel off or crack. As a result, the corrosion-resistant member according to the present embodiment has excellent corrosion resistance even when subjected to a thermal history, and the generation of particles resulting from the peeling of the corrosion-resistant coating 30 is suppressed.
[0016] The corrosion-resistant member according to this embodiment is suitable as a member that requires corrosion resistance and heat resistance, for example, as a member constituting a semiconductor manufacturing apparatus (particularly, a film-forming apparatus using a chemical vapor deposition method). As a specific example, it is suitable as a susceptor or shower head of a film-forming apparatus that forms a thin film on a wafer while plasma is generated. If the corrosion-resistant member according to this embodiment is used as a member constituting a semiconductor manufacturing apparatus, the generation of particles is suppressed, and semiconductors can be manufactured with a high yield.
[0017] The corrosion-resistant member of this embodiment can be manufactured, for example, by forming a magnesium fluoride layer 31 on the surface of a substrate 10, and then forming a first crystalline layer 32A, an amorphous layer 32B, and a second crystalline layer 32C in this order on the magnesium fluoride layer 31 to form an aluminum fluoride layer 32.
[0018] The magnesium fluoride layer 31 can be formed by a method such as vacuum deposition or sputtering. The first crystalline layer 32A and the second crystalline layer 32C of the aluminum fluoride layer 32 can also be formed by a method such as vacuum deposition or sputtering, and the crystallinity of the aluminum fluoride layer can be increased by controlling the temperature of the object on which the aluminum fluoride layer is formed to a high temperature. The amorphous layer 32B can be formed by a method such as a vapor deposition method (physical vapor deposition (PVD), chemical vapor deposition (CVD), etc.), and the crystallinity of the aluminum fluoride layer can be suppressed by controlling the temperature of the object on which the aluminum fluoride layer is formed to a low temperature.
[0019] The corrosion-resistant member according to this embodiment will be described in further detail below. The metal constituting the base material 10 is not particularly limited, and may be a simple metal (containing unavoidable impurities) or an alloy, such as aluminum or an aluminum alloy.
[0020] The thickness of the magnesium fluoride layer 31 is preferably 100 nm or more and 1000 nm or less. If the thickness of the magnesium fluoride layer 31 is within the above range, the adhesion between the aluminum fluoride layer 32 and the substrate 10 will be higher. The thickness of the aluminum fluoride layer 32, i.e., the total thickness of the first crystalline layer 32A, the second crystalline layer 32C, and the amorphous layer 32B, is preferably 200 nm or more and 50,000 nm or less. If the thickness of the aluminum fluoride layer 32 is within the above range, the corrosion-resistant coating 30 is more resistant to peeling when subjected to a thermal history.
[0021] The method for measuring the thickness of the magnesium fluoride layer 31 and the aluminum fluoride layer 32 is not particularly limited, and examples thereof include a method using a transmission electron microscope (TEM), a scanning transmission electron microscope (STEM), a scanning electron microscope (SEM), etc. The thicknesses of the first crystalline layer 32A, the amorphous layer 32B, and the second crystalline layer 32C can also be measured by a similar method.
[0022] The elements such as magnesium and aluminum present in the magnesium fluoride layer 31 and the aluminum fluoride layer 32 can be quantified by, for example, energy dispersive X-ray analysis (EDS analysis). The presence of crystalline or amorphous aluminum fluoride in the first crystalline layer 32A, the amorphous layer 32B, and the second crystalline layer 32C can be analyzed by electron beam diffraction (electron beam diffraction image obtained by irradiating with an electron beam). The conditions for the electron beam diffraction method in the present invention are as follows. That is, a sample processed to a thickness of 40 nm to 100 nm using an ion slicer is used, the beam diameter of the electron beam is set to 10 nm to 20 nm, and an electron beam diffraction image is obtained using a TEM. EXAMPLES
[0023] The present invention will be described more specifically below with reference to examples and comparative examples. Example 1 The substrate was first pretreated, and then vacuum deposition was performed to form a magnesium fluoride layer on the surface of the substrate, and then a first crystalline layer, an amorphous layer, and a second crystalline layer were formed in this order on the magnesium fluoride layer to form an aluminum fluoride layer, thereby obtaining a corrosion-resistant member. The first crystalline layer and the second crystalline layer were formed by thermal deposition, and the amorphous layer was formed by room temperature deposition.
[0024] The metal constituting the substrate is an aluminum alloy A5052 containing 2.55% by mass of magnesium. The pretreatment of the substrate was performed as follows. First, 70 g of S-clean AL-13 (manufactured by Sasaki Chemical Co., Ltd.) was dissolved in 1 L of water and the temperature was adjusted to 50° C. to prepare a degreasing liquid. The substrate was immersed in this degreasing liquid for 10 minutes to perform degreasing, and then washed with pure water. Next, 500 g of S-clean AL-5000 (manufactured by Sasaki Chemical Co., Ltd.) was heated to 70° C. to prepare an etching liquid. The degreased substrate was immersed in this etching liquid for 1 minute to perform etching, and then washed with pure water. After that, 200 g of Smut Clean (Raiki Co., Ltd.) was dissolved in 400 g of water and the temperature was adjusted to 25° C. to prepare a smut removal liquid. The etched substrate was immersed in this smut removal liquid for 30 seconds to perform smut removal, and then washed with pure water. Then, the substrate from which the smut was removed was vacuum-dried to complete the pretreatment.
[0025] The conditions for vacuum deposition when forming the magnesium fluoride layer are as follows: First, the pretreated substrate is placed in a vacuum chamber, and then the vacuum degree is 2×10 -4 The vacuum chamber was evacuated until the pressure reached 10 Pa. The pretreated substrate was then heated to 380°C. A magnesium fluoride sintered material was used as the deposition material, and an electron beam was irradiated onto the sintered material. The shutter was opened, and a magnesium fluoride layer of approximately 235 nm in thickness was formed on the pretreated substrate. The input power of the electron beam was approximately 40 mA at an acceleration voltage of 5 kV, and the degree of vacuum during deposition was 5×10 -4 The name was Pa.
[0026] The deposition conditions for forming the first crystalline layer are as follows: First, the substrate on which the magnesium fluoride layer is formed is placed in a vacuum chamber, and then the vacuum degree is set to 2×10 -4The vacuum chamber was evacuated until the pressure reached 100 Pa. The substrate on which the magnesium fluoride layer was formed was then heated to 400°C. An aluminum fluoride sintered material was used as the deposition material, and an electron beam was irradiated onto this sintered material. A shutter was opened, and an aluminum fluoride layer with a thickness of 236 nm was formed as a first crystalline layer on the magnesium fluoride layer of the substrate heated to 400°C. The input power of the electron beam at this time was about 40 mA at an acceleration voltage of 5 kV, and the degree of vacuum during deposition was 5×10 -4 The name was Pa.
[0027] The deposition conditions for forming the amorphous layer are as follows: First, the substrate on which the first crystalline layer is formed is placed in a vacuum chamber, and then the vacuum degree is 2×10 -4 The vacuum chamber was evacuated until the vacuum pressure reached 10 Pa and then maintained at room temperature. An aluminum fluoride sintered material was used as the deposition material, and an electron beam was irradiated onto this sintered material. The shutter was opened, and an aluminum fluoride layer with a thickness of about 451 nm was formed as an amorphous layer on the first crystalline layer of the substrate maintained at room temperature. The input power of the electron beam at this time was about 40 mA at an acceleration voltage of 5 kV, and the degree of vacuum during deposition was 5×10 -4 The name was Pa.
[0028] The deposition conditions for forming the second crystalline layer were the same as those for the first crystalline layer. The substrate having an amorphous layer formed on the first crystalline layer was heated to 400°C, and an aluminum fluoride layer having a thickness of approximately 249 nm was formed as the second crystalline layer on the amorphous layer of the substrate heated to 400°C. After forming the first crystalline layer, the amorphous layer, and the second crystalline layer, the substrate was heated to 350°C in an atmosphere of 20% fluorine gas (the remaining 80% being nitrogen gas) to replenish the missing fluorine atoms generated during the deposition.
[0029] The elements such as magnesium, aluminum, etc. present in the formed magnesium fluoride layer and aluminum fluoride layer were analyzed by EDS. More specifically, a sample was processed with an ion slicer to a thickness of 40 nm to 100 nm, and point analysis of each layer was performed at an accelerating voltage of 200 V to analyze the elements such as magnesium, aluminum, etc. The presence of crystalline or amorphous aluminum fluoride in the first crystalline layer, the amorphous layer, and the second crystalline layer was confirmed by electron beam diffraction. More specifically, a sample processed to a thickness of 40 nm to 100 nm using an ion slicer was irradiated with an electron beam having a beam diameter of 10 nm to 20 nm, and an electron beam diffraction image was obtained using a TEM. The electron beam diffraction images of the first crystalline layer, the amorphous layer, and the second crystalline layer are shown in Figures 2, 3, and 4, respectively.
[0030] A heating test was performed to evaluate the state of peeling of the corrosion-resistant coating on the obtained corrosion-resistant member of Example 1. The heating test was performed under the conditions of 10 cycles, each cycle consisting of holding at 300°C for 300 minutes in a nitrogen gas atmosphere and then naturally cooling to room temperature. After the heating test was completed, the corrosion-resistant coating of the corrosion-resistant component was observed with a scanning electron microscope to evaluate the degree of peeling. The results are shown in Table 1. In Table 1, if the area of the peeled part of the corrosion-resistant coating was less than 1% of the area of the corrosion-resistant coating, it is indicated as A, if it was 1% or more but less than 10%, it is indicated as B, if it was 10% or more but less than 50%, it is indicated as C, and if it was 50% or more, it is indicated as D.
[0031] Furthermore, a corrosion test was carried out on the obtained corrosion-resistant member of Example 1 to evaluate the state of peeling of the corrosion-resistant coating. The corrosion test was carried out by carrying out a heat treatment in an inert gas atmosphere containing fluorine gas (F2), under the conditions that the concentration of fluorine gas in the inert gas atmosphere was 1 volume %, the heat treatment temperature was 300°C, and the heat treatment time was 300 min.
[0032] After the corrosion test was completed, the surface of the corrosion-resistant coating of the corrosion-resistant component was observed with a scanning electron microscope to evaluate the degree of peeling. The results are shown in Table 1. In Table 1, if the area of the peeled portion of the corrosion-resistant coating was less than 1% of the area of the corrosion-resistant coating, it is indicated as A, if it was 1% or more but less than 10%, it is indicated as B, if it was 10% or more but less than 50%, it is indicated as C, and if it was 50% or more, it is indicated as D. The numbers in Table 1 indicate the thickness of each layer, and "-" indicates that the layer in question was not formed.
[0033] [Table 1]
[0034] Comparative Example 1 A corrosion-resistant member was manufactured and evaluated in the same manner as in Example 1, except that only the first crystalline layer and the amorphous layer were formed as the aluminum fluoride layer on the magnesium fluoride layer, and the second crystalline layer was not formed. The results are shown in Table 1. Comparative Example 2 A corrosion-resistant member was manufactured and evaluated in the same manner as in Example 1, except that only the first crystalline layer and the second crystalline layer were formed as the aluminum fluoride layer on the magnesium fluoride layer, and no amorphous layer was formed. The results are shown in Table 1.
[0035] Comparative Example 3 A corrosion-resistant member was manufactured and evaluated in the same manner as in Example 1, except that only an amorphous layer and a second crystalline layer were formed as an aluminum fluoride layer on the magnesium fluoride layer, and the first crystalline layer was not formed. The results are shown in Table 1. Comparative Example 4 Except for not forming a magnesium fluoride layer on the surface of the substrate, a corrosion-resistant member was produced and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0036] Comparative Example 5 A corrosion-resistant member was manufactured and evaluated in the same manner as in Example 1, except that only the first crystalline layer was formed as the aluminum fluoride layer on the magnesium fluoride layer, and neither the amorphous layer nor the second crystalline layer was formed. The results are shown in Table 1. Comparative Example 6 Except for not forming an aluminum fluoride layer on the magnesium fluoride layer, a corrosion-resistant member was produced and evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0037] As can be seen from Table 1, in Example 1, the corrosion-resistant coating hardly peeled off even when subjected to the thermal history in the heating test. Also, even when subjected to corrosion in the corrosion test, the corrosion-resistant coating hardly peeled off. In contrast, in Comparative Examples 1 and 6, which do not have an aluminum fluoride crystalline layer on the surface, peeling of the corrosion-resistant coating occurred during the corrosion test. In particular, Comparative Example 1, which has an amorphous layer on the outermost surface, is easily corroded by fluorine gas. Also, Comparative Example 6, which has a magnesium fluoride layer on the outermost surface, is found to have lower corrosion resistance than Example 1, which has an aluminum fluoride crystalline layer on the outermost surface.
[0038] In Comparative Example 4, in which an aluminum fluoride layer was formed directly on a metal substrate without a magnesium fluoride layer therebetween, peeling occurred at the interface when the temperature was repeatedly increased and decreased. In Comparative Example 2, in which there was no amorphous layer between the first and second crystalline layers, cracks occurred in the lamination direction of the aluminum fluoride layer when the temperature was repeatedly increased and decreased, resulting in peeling. From this result, it is expected that the amorphous layer contributes to mitigating stress caused by temperature changes.
[0039] Comparative Example 5, in which only the first crystalline layer exists on the magnesium fluoride layer, was more likely to develop cracks due to repeated heating and cooling than Example 1, and peeling occurred from these cracks. From this result, it is expected that the amorphous layer contributes to mitigating stress caused by temperature changes. In Comparative Example 3 in which an amorphous layer exists on a magnesium fluoride layer, peeling was likely to occur at the interface due to repeated temperature increases and decreases. [Explanation of symbols]
[0040] 10...Base material 30. Corrosion-resistant coating 31 Magnesium fluoride layer 32 Aluminum fluoride layer 32A: First crystalline layer 32B: Amorphous layer 32C: Second crystalline layer
Claims
1. A metal substrate and a corrosion-resistant coating formed on a surface of the substrate, the corrosion-resistant coating is formed by laminating, in this order from the substrate side, a magnesium fluoride layer containing magnesium fluoride and an aluminum fluoride layer containing aluminum fluoride, the aluminum fluoride layer is a layer formed by laminating, in this order from the magnesium fluoride layer side, a first crystalline layer containing crystalline aluminum fluoride, an amorphous layer containing amorphous aluminum fluoride, and a second crystalline layer containing crystalline aluminum fluoride, the first crystalline layer and the second crystalline layer are layers in which diffraction spots are observed in an electron beam diffraction image obtained by irradiating the layers with an electron beam, the amorphous layer is a layer in which a halo pattern is observed in an electron beam diffraction image obtained by irradiating the layer with an electron beam, A corrosion-resistant member, wherein the amorphous layer has a thickness of 451 nm or more.
2. 2. The corrosion-resistant member according to claim 1, wherein the metal substrate is made of aluminum or an aluminum alloy.
3. 3. The corrosion-resistant member according to claim 1, wherein the magnesium fluoride layer has a thickness of 100 nm or more and 1000 nm or less.
Citation Information
Patent Citations
Vacuum chamber member and its production
JP1999061410A
Halogen gas resistant member and its manufacturing method
JP2004319803A
Articles with protective coatings used in semiconductor processing chambers and methods of making same
JP2005533368A
Plasma device
JP2009117373A
Corrosion-resistant aluminum article for semiconductor processing equipment
JP2009256800A